GLOBAL EXPERIENCE OF PUBLIC FINANCIAL CONTROL IN THE PUBLIC FINANCIAL MANAGEMENT SYSTEM - YAROVA, Yuliia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The relevance of this study lies in the fact that with the transition of the economy to a market model, state control over the legality and rationality of the use of public finance becomes increasingly important. State financial control is an important instrument of the financial mechanism and one of the main means of implementing state financial policy. Its role is to support the successful implementation of financial strategy and tactics, as well as the expedient and efficient formation, allocation and use of financial resources of the state. In the conditions of formation of a market economy, control over the budgetary process is becoming increasingly important due to the need to improve the efficiency ofpublic administration of the whole system offinancial relations. State financial control includes control over compliance with financial legislation, the process offormation and use of state, budgetary and extra-budgetary resources, as well as assessment of the economic efficiency offinancial operations and the targeted nature of public expenditure. This work covers important theoretical and methodological aspects of state financial control and aims to identify the main directions of its development abroad. The paper analyses foreign experience in three areas: general public finance control, parliamentary and government control as well as internal control and internal audit as special areas of financial control.
Keywords: public finance management; types of state financial control; state financial control; foreign experience; methods of state financial control; state financial control bodies; financial management system; forms of state financial control